Leg Strength is Associated with Ventilatory Efficiency in Older Women - Gonzales, J. U.; Tucker, S. H.; Kalasky, M. J.; Proctor, D. N. (International Journal of Sports Medicine, 2012)
The aim of the present study was to determine if leg function is associated with ventilatory efficiency during exercise in healthy older adults. 24 women and 18 men aged 60–80 years performed treadmill exercise to fatigue for calculation of ventilatory efficiency using the ratio of ventilation to carbon dioxide at the anaerobic threshold (VE/VCO2@AT). On a separate day, participants performed leg strength testing and graded single-leg knee extension exercise. The VE/VCO2@AT was higher in women than men (33±3 vs. 30±3; p=0.03). After adjustment for age and VO2max, leg strength (knee extensor isometric force) was inversely associated with VE/VCO2@AT in women (r= − 0.44, p=0.03) while no relationships were found for men. Strength-matched women and men had similar VE/VCO2@AT indicating that the correlation between leg strength and VE/VCO2@AT was strength- but not sex-specific. During knee extensor exercise, women with lower leg strength had increased VE/VCO2 slope across 0–15 W as compared to higher strength women (38±8 vs. 31±3; p<0.05), while no differences were found for men. These results find leg strength to be associated with ventilatory responses to exercise in healthy older women, a finding that might be related to lower leg strength in women than men.
Keywords: aging; ventilation; sex differences; muscle strength